Analisis Manajemen Risiko Layanan Mobile Banking Pada Bank Syariah - Sukma Oktaviani; Nuhbatul Basyariah (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
The development of information and communication technology today has made the banking industry compete fiercely in creating innovative electronic products and services in transactions, one of which is with mobile banking products. As a service product, and an integral part of bank operational activities, mobile banking has risks in its use. This study aims to analyze the types of risks in mobile banking services and analyze the various efforts of Islamic banks in solving them. The analytical method used is descriptive qualitative method, with a library study approach or literature review. The results of the research of various banks that have used mobile banking services have risk mitigation mechanisms and efforts to prevent risks arising from mobile banking services, so that people do not need to worry too much about mobile banking services from Islamic banks.